2011
DOI: 10.1007/s12600-011-0178-0
|View full text |Cite
|
Sign up to set email alerts
|

New records of mealybugs (Hemiptera: Pseudococcidae) from Spain

Abstract: Five mealybug (Hemiptera: Pseudococcidae) species were identified as new records for Spain: Phenacoccus madeirensis (Green), Phenacoccus solani Ferris, Dysmicoccus boninsis (Kuwana), Hypogeococcus pungens Granara de Willink and Ferrisia malvastra (McDaniel).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…This species has been reported from South America, Australia, South Africa, Italy, Spain, Saint Thomas in the U.S. Virgin Islands, Barbados, United States (Florida, California, and Hawaii), and Puerto Rico ( McFadyen and Tomley 1978 , 1981, Tomley and McFadyen 1984 , Hosking et al 1988 , Moran and Zimmermann 1991 , Halbert 1996 , Klein 1999 , Mazzeo et al 2008 , Hodges and Hodges 2009 , Zimmermann and Pérez Sandi y Cuen 2010 , Beltrà and Soto 2011 ). Although it is not known how H. pungens colonized areas where it was not deliberately released, it is suspected that it was introduced via the trade of ornamental cacti ( Zimmermann and Pérez Sandi y Cuen 2010 ).…”
mentioning
confidence: 91%
“…This species has been reported from South America, Australia, South Africa, Italy, Spain, Saint Thomas in the U.S. Virgin Islands, Barbados, United States (Florida, California, and Hawaii), and Puerto Rico ( McFadyen and Tomley 1978 , 1981, Tomley and McFadyen 1984 , Hosking et al 1988 , Moran and Zimmermann 1991 , Halbert 1996 , Klein 1999 , Mazzeo et al 2008 , Hodges and Hodges 2009 , Zimmermann and Pérez Sandi y Cuen 2010 , Beltrà and Soto 2011 ). Although it is not known how H. pungens colonized areas where it was not deliberately released, it is suspected that it was introduced via the trade of ornamental cacti ( Zimmermann and Pérez Sandi y Cuen 2010 ).…”
mentioning
confidence: 91%
“…The host plants used by the Harrisia cactus mealybug introduced as a biological control agent into Australia and South Africa consist only of species in Cactoideae (Zimmermann & Pérez Sandi y Cuen 2010;McFadyen 2012;. In addition to these 2 countries, the distribution of H. pungens has expanded, due to inadvertent introductions from its apparently native South America, to locations in Italy, Spain, US Virgin Islands, Barbados, the Dominican Republic, Puerto Rico, and the USA states of Florida, California, and Hawaii (Hosking et al 1988;Halbert 1996;Mazzeo et al 2008;Hodges & Hodges 2009;Zimmermann & Pérez Sandi y Cuen 2010;Beltrà & Soto 2011;German-Ramirez et al 2014). The host range of the Harrisia cactus mealybug identified as H. pungens includes species of plants in the families Cactaceae, Amaranthaceae, and Portulacaceae (Ben-Dov 1994;Claps & de Haro 2001;Hodges & Hodges 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Identified for the Madeira mealybug Phenacoccus madeirensis Green, (Hemiptera: Pseudococcidae) by Bader and Moharum (2017), was the first time in Egypt. This species was recorded in Italy by Marotta & Tranfaglia (1990) and more recently in France (Matile-Ferrero & Germain, 2004), Mediterranean region (Williams, 2004) Crete (Jansen et al, 2010), Portugal (Franco et al, 2011),Spain (Beltra & Soto, 2011), mainland Greece (Papadopoulou & Chryssohoides, 2012), Turkey (Kaydan et al, 2012), and Tunisia (Halima-Kamel et al, 2014). reported that it is could be Neotropical in origin and has now invaded parts of the Afrotropical, Neotropical, Nearctic, Australasian and Oriental Zoogeographical Regions.…”
Section: Introductionmentioning
confidence: 84%